2018
DOI: 10.1007/s00104-018-0732-0
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan-beschichtete Nahtmaterialien in der kolorektalen Chirurgie

Abstract: Against the background of a moderate to high risk of bias and the partially contradictory findings of the studies, the general recommendation of the WHO on the use of triclosan-coated sutures for colorectal surgery could not be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Triclosan [5-chloro-2-(2,4-dichlorophenoxy)phenol; TCS] is a bactericidal and antifungal agent that is ubiquitously incorporated into thousands of industrial and consumer products including clothing, toys, cleaning supplies, personal care products (i.e., soap, shampoo, toothpaste, etc. ), and surgical soaps and sutures (52, 53) with 10.5 million pounds produced globally in 2015 (53). Triclosan and triclocarban (TCC), another widely used antibacterial in PPCPs, are the most common, broad-spectrum antimicrobial agents used in household items and PPCPs (54).…”
Section: Pharmaceuticals and Personal Care Productsmentioning
confidence: 99%
“…Triclosan [5-chloro-2-(2,4-dichlorophenoxy)phenol; TCS] is a bactericidal and antifungal agent that is ubiquitously incorporated into thousands of industrial and consumer products including clothing, toys, cleaning supplies, personal care products (i.e., soap, shampoo, toothpaste, etc. ), and surgical soaps and sutures (52, 53) with 10.5 million pounds produced globally in 2015 (53). Triclosan and triclocarban (TCC), another widely used antibacterial in PPCPs, are the most common, broad-spectrum antimicrobial agents used in household items and PPCPs (54).…”
Section: Pharmaceuticals and Personal Care Productsmentioning
confidence: 99%
“…In addition, Henriksen's meta-analysis evaluated several forms of surgery, including elective open colorectal surgery, elective midline laparotomy, open appendectomy, and even faecal peritonitis laparotomies [22,25]. In their meta-analyses, Edmiston et al, Chang et [21,22,[26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…20,23 Other meta-analyses pooled all available randomized controlled trials without categorizing the risk by wound class, kind of operation, or organ or apparatus implicated. 19,20,[24][25][26][27][28][29] Different studies have been conducted and demonstrated the superiority of triclosan. In vitro, preclinical studies have demonstrated that coated polyglactin 910 sutures effectively inhibit the growth of Staphylococcus aureus, Staphylococcus epidermidis, methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant Staphylococcus epidermidis (MRSE).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Henriksen's meta‐analysis evaluated several forms of surgery, including elective open colorectal surgery, elective midline laparotomy, open appendicectomy and even faecal peritonitis laparotomies 20,23 . Other meta‐analyses pooled all available randomized controlled trials without categorizing the risk by wound class, kind of operation, or organ or apparatus implicated 19,20,24–29 …”
Section: Discussionmentioning
confidence: 99%